Industry and academia networks - Romero, Fernando (2008)
Universities have historically been a source of fundamental knowledge, and the premier source of technologies that have found innumerable applications (in the economy, in the military, in health care, etc.) and that have shaped the trajectory, the direction and the nature of social and economic development. The contribution of universities towards the economic fabric of a region, nation or supranational entity is manifold, and is recognised as essential to the creation of wealth. It is because of that recognition that there has been a growing need to understand in what ways knowledge created at the universities is transferred and it impacts upon society at large. Knowledge can take many forms, and the resources devoted to knowledge creation can themselves be allocated to different levels and degrees of activities related to that endeavour. However, resources are scarce and resource allocation to knowledge must be essentially of a long- range perspective. The distribution of resources in terms of short-range and long-range investment in knowledge is inextricably linked to the phenomena of university-industry relations. Many initiatives fostering linkages between universities and industry, with a view to increase or facilitate rates of technology transfer, implemented innovation and economic development. However, the contexts in which these relations occur vary broadly and presently, because resources for investment in knowledge creation are scarce and differentiated there is a need for a comprehensive understanding of the variety of initiatives and relationships that exist, and the need for a deeper conceptualization of the forms, configurations, roles and expectations that shape and define existing relationships.